The study of administrative history Philippine Public Administration as an ahistorical discipline - Reyes, Danilo R. (Philippine journal of public administration)
In recent years, more than fifty years from the time Waldo observed the ahistorical nature of the discipline in America, there has been a growing number of literature that looks into the past with the intention of understanding its implications for the present. Of late, there is an incipient subfield of administrative history that has managed to gain attention of Public Administration scholarship in America. Unfortunately, the study of administrative history in the Philippines has not fully developed in spite of some scattered efforts of its scholars to chronicle the past and its impact on the present. This article calls attention to engendering a study of administrative history in the Philippines. It suggests that this question can be answered with more confidence if it looks to the significance of the historical past that can serve as empirical referents in identifying and explaining the peculiarities and particulars of the study and practice of public administration in the country. Further, it reviews the literature on administrative history in the United States and in the Philippines while citing important historical events that can be considered in appreciating and understanding the discipline and the practice of public administration as it has evolved and developed in the Philippines.